P204 Immune Responses To Single And Repeated Administration Of Pgm169/gl67a: The Uk Cf Gene Therapy Consortium Clinical Trials. (10th November 2014) - Griesenbach, U; Boyd, AC; Calcedo, R; Cheng, S; Cunningham, S; Davies, JC; Dewar, M; Gill, DR; Doherty, A; Higgins, T; Hyde, SC; Manvell, M; et al.
Abstract : Although most CF patients express CFTR protein (albeit mutant) and should therefore not recognise the wild-type CFTR protein as foreign, there is an inherent risk of activation of T-cells against the recombinant wild-type protein after gene therapy. In addition, we have previously shown that approximately 10% of CF and non-CF subjects carry self-reactive CFTR-specific T-cells ( Calcedo et al, Hum Gene Ther Clin Dev 2013 ). The reason for this is unknown and it is also unclear whether being positive for self-reactive T-cells affects disease severity or increases the risk of further T-cell activation after gene therapy. As part of the UKCFGTC Phase I/IIa Pilot study [in which patients received a single dose (5, 10 or 20 mls) of the non-viral formulation pGM169/GL67A] peripheral blood mononuclear cells (PBMC) were collected prior to dosing and approximately 4 weeks after nebulisation of 5 ml (n = 2), 10 ml (n = 6) or 20 ml (n = 17) of pGM169/GL67A. IFN-g ELISPOT to detect CFTR-specific T-cells in PBMC was performed. CFTR-specific T-cells were detectable in one patient pre- and post-dosing. In the remaining 18 patients we did not detect CFTR-specific T-cells. In addition we quantified anti-DNA antibodies (anti-nuclear and anti-cytoplasmic) in blood samples taken pre- and approximately 4 weeks post-dosing (n = 7 (5 ml), n = 10 (10 ml) and n = 17 (20 ml). We did not observe any evidence for induction of anti-DNA antibodies after a single dose of pGM169/GL67A. The UKCFGTC has now completed a Phase IIb multi-dose clinical trial in May 2014 (ClinicalTrials.gov identification number – NCT01621867 ). CF patients received 12 monthly doses of pGM169/GL67A (115 completed nine or more doses), or placebo by aerosol. PBMC were collected on two occasions prior to dose 1 to establish baseline levels for CFTR-specific T-cells, approximately 4 weeks after Dose 4 or 5, and 2 to 4 weeks after Dose 12 and the ELISPOT was performed. In addition anti-DNA antibodies were quantified. The Phase IIb trial will be unblinded in Summer 2014 to allow data analysis and all data will be presented at the conference. Funded by the NIHR/EME Programme and the Cystic Fibrosis Trust.